Tumor Profiling at the Service of Cancer Therapy - Fernandez-Rozadilla, Ceres; Simões, Ana Rita; Lleonart, Matilde E.; Carnero, Amancio; Carracedo, Ángel (Frontiers in Oncology, 2021)
Cancer treatment options have evolved significantly in the past few years. From the initial surgical procedures, to the latest next-generation technologies, we are now in the position to analyse and understand tumours in a one-by-one basis and use that to our advantage to provide with individualised treatment options that may increase patient survival. In this review, we will focus on how tumour profiling has evolved over the past decades to deliver more efficient and personalised treatment options, and how novel technologies can help us envisage the future of precision oncology towards a better management and, ultimately, increased survival.